The The Effectiveness Of The Leader's Operational Management In Managing Logistics And Equipment At The Bandar Lampung City Bpbd Office - Randi Prasetyo; Vonny Tiara Narundana (International Journal of Economics, Business and Innovation Research, 2024)
Local governments have an obligation to mitigate the suffering of those affected by disasters as part of disaster management efforts. Operational management is essential to carry out logistics and equipment management. Ensuring the allocation of disaster relief in Bandar Lampung City is in accordance with Law No. 13 of 2008 which outlines the guidelines for the management of regional disaster logistics and equipment. The purpose of the writing is to determine the effectiveness of the operational management of the leadership and find possible improvements and suggestions to increase the efficiency of supply and increase understanding of the management of disaster relief supplies and equipment in the field of logistics to provide valuable input to BPBD Bandar Lampung City to improve its performance. The research includes a field survey, interviews with three personnel of BPBD Bandar Lampung City, namely the Head of Division and 2 logistics and equipment staff and conducting data analysis. The equipment of BPBD Bandar Lampung City is currently not fully functional. Although the efforts of BPBD Bandar Lampung City are appreciated, there are still challenges in its implementation due to lack of resources. Consequently, the agency has to rely on the facilities of other relevant organizations to ensure smooth operational management of logistics and equipment.